Features of projects for the establishment of protected areas for the protection of agricultural lands in the Khavos district of the Syrdarya region (Eurasian Journal of Engineering and Technology, 2026)
This article analyzes the causes, effects, and countermeasures of arable land degradation, which is currently becoming a global environmental problem, the stages of developing projects for the organization of green spaces and land development projects, and several important factors in the use of land resources.